The Relationship Between Self-Efficacy and Nurse Performance in The Inpatient Ward at Mawaddah Medika Hospital - Riza Patmawati Dewi; Windu Santoso; Dwi Basuki; Noor Fatima (CV Media Inti Teknologi, 2025)
Background of study: Hospitals are essential in delivering healthcare, and the quality of their services largely depends on the people working in them, especially nurses. Nurses’ confidence in their own abilities, known as self-efficacy, greatly impacts not only how well they care for patients but also the overall success of the hospital.Aims and scope of paper: This research seeks to explore how nurses’ self-efficacy relates to their performance in the inpatient ward at Mawaddah Medika Hospital.Methods: This study used a quantitative approach with descriptive correlational design and a cross-sectional snapshot in time. Forty-five nurses participated, selected through proportional random sampling. Data were gathered using the General Self-Efficacy Scale (GSES) alongside a questionnaire measuring nurse performance. The relationship between variables was analyzed using Spearman’s rank correlation.Results: The majority of nurses reported feeling confident in their abilities (60.0%) and showed strong job performance (53.3%). Statistical analysis showed a significant and strong positive link between their self-confidence and their work performance, with a correlation score of 0.792 and a highly significant p-value (p < 0.05).Conclusion: The results underline the importance of boosting nurses’ confidence to enhance their performance in the inpatient ward. Key factors that support this improvement include hands-on experience, supportive work environments, emotional coping skills, clear roles and responsibilities, ongoing assessments, and continuous training programs.